CHARACTER EDUCATION THROUGH HISTORY LEARNING ON NONFORMAL EDUCATION - Ranulin Windarsari (Proceedings Education and Language International Conference, 2017)
The purpose of this paper is to describe the role of teaching history in shaping the character of the Indonesian nation through non-formal education. Non-formal education can be defined as the path of education outside formal education can be structured and tiered. Non-formal education includes life skills education, early childhood education, equality education, literacy, and others. KTSP prevailing in Indonesia demanding character education in it. Learning history in a strategic significance in the formation of character and civilization of the nation's dignity as well as in the formation of Indonesian people who have a sense of nationalism and patriotism. State residents to learn as learners in non-formal education that is different from that of students in the formal education also needs to be invested in the character value for a state of non-formal education learners more flexibility for the implementation of character education through the teaching of history with combined with the characteristic possessed on non-formal education are provided with vocational skills to support the creativity and work of learners. In this study the authors used data obtained from books, journals, articles, and websites of various media such as print and electronic media. The theory used in this research is the study of history, character education, non-formal education.Keywords: Character Education, Learning History, Non-formal Education